The impact of enterprise resource planning system on Iranian firms performance - Parto, Ali (2017)
In the past two decades, there has been a significant growth market for Enterprise Resource Planning (ERP) in developing countries. However, due to recent economic development of these countries such as Iran, the demand for ERP systems increased considerably. Besides these growths, failures in ERP implementation also have been increased. Therefore, there is an urgent need for understanding ERP implementation and post evaluation issues in developing countries. The main objectives of this study is to identify common ERP modules, critical success factors (CSFs) of ERP implementation among the manufacturing firms in Iran in order to assess the impact of ERP systems implementation on performance across four perspectives (financial, customer, internal process and learning) of the balanced scorecard (BSC). For this purpose, a theory-based model has been developed to examine the relationship between ERP system status and firms performance perspectives. Empirical analyses are based on survey data drawn from 93 Iranian manufacturing firms, which have adopted ERP systems for at least a year. Structural equation modeling (SEM) is employed to test the research hypotheses and Fuzzy DEMATEL method is applied to find the impact of ERP implementation modules and performance indicators. The result indicates that there is a positive significant relationship between ERP system status and changes in financial, customer and learning perspectives of performance. In addition, CSFs and ERP modules on performance perspectives indicated a positive interaction. On the other hand, fuzzy DEMATEL analysis shows, sale and distribution module of ERP had the strongest impact on performance within Iranian manufacturing firms. Consequently, the managers who want to implement ERP systems can use the ranking to choose suitable ERP modules. The results of the study suggest that firms that emphasize CSFs throughout the ERP implementation process achieve higher performance improvement. Further research should gather data from various sources and also from the service sectors.